A new Plotosaurini mosasaur skull from the upper Maastrichtian of Antarctica. Plotosaurini paleogeographic occurrences - González Ruiz, Pablo (2019)
Fil: Gonzáles Ruiz, Pablo. Museo de Historia Natural de San Rafael. Grupo vinculado del IANIGA. Mendoza, Argentina.